Impacto da laserterapia de baixa potência na hipossalivação, pH salivar e qualidade de vida de pacientes após radioterapia para câncer de cabeça e pescoço - Palma, Luiz Felipe [UNIFESP] (2017)
Purpose: To evaluate the effect of low-level laser therapy on hyposalivation, salivary pH, and quality of life in head and neck cancer patients post-radiotherapy. Methods: Twenty-nine patients with radiation-induced xerostomia received laser sessions twice a week, during three months (24 sessions). For this, a continuous wave Indium-Gallium-Aluminium-Phosphorus diode laser device was used punctually (808 nm, 0.75 W/cm², 30 mW, illuminated area 0.04 cm², 7.5 J/cm², 10 seconds, 0.3 J) on the major salivary glands. Six extraoral points were illuminated on each parotid gland and three on each submandibular gland, as well as two intraoral points on each sublingual gland. Stimulated and unstimulated salivary flow rates, pH (two scales with different gradations), and quality of life (University Of Washington Quality of Life Questionnaire for Patients with Head and Neck Cancer) were assessed at baseline and at the end of the treatment. Results: There were significant increases in both mean salivary flow rates (unstimulated: p=0.0012; stimulated: p<0.0001), mean pH values (p=0.0002 and p=0.0004), and mean score from the quality of life questionnaire (p<0.0001). Conclusion: Low-level laser therapy was able to mitigate hyposalivation and increase salivary pH of patients submitted to radiotherapy for head and neck cancer, thereby contributing to an evident improvement in quality of life.